IMPLEMENTASI KEBIJAKAN PENGGUNAAN BANTUAN KEUANGAN PARTAI POLITIK OLEH DEWAN PIMPINAN CABANG PDI PERJUANGAN KOTA DEPOK TAHUN 2021-2023 - Ayomi, Thephilus Lukas (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to analyze and describe the Standards and objectives, Supporting resources, Communication and strengthening activities between organizations, Characteristics of implementing positions in management, Political and social economic conditions, and Disposition of implementers in managing political party financial assistance by the Depok City Branch Leadership Council of the Indonesian Democratic Party of Struggle. This study uses a descriptive method with a qualitative approach, with data collection techniques through observation and interviews. Data analysis techniques are carried out through data collection, data presentation and drawing conclusions. Based on the results of the study and discussion above, overall it can be concluded that the implementation of the policy on the use of political party financial assistance by the Depok City Branch Leadership Council of the Indonesian Democratic Party of Struggle is right on target, namely for political education. This is based on the fulfillment of the six variables of the Policy Implementation Model proposed by Van Meter & Van Horn which include; (1) Standards and objectives, (2) Supporting resources, (3) Communication and strengthening activities between organizations, (4) Characteristics of implementing positions, (5) Economic, political, and social support, and (6) Disposition of implementers.